Proceedings of the 57th Annual Meeting of the Association for Computational Linguistics 2019
DOI: 10.18653/v1/p19-1299
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Source Cross-Lingual Model Transfer: Learning What to Share

Abstract: Modern NLP applications have enjoyed a great boost utilizing neural networks models. Such deep neural models, however, are not applicable to most human languages due to the lack of annotated training data for various NLP tasks. Cross-lingual transfer learning (CLTL) is a viable method for building NLP models for a low-resource target language by leveraging labeled data from other (source) languages. In this work, we focus on the multilingual transfer setting where training data in multiple source languages is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 37 publications
1
83
0
Order By: Relevance
“…Our results show that even a simple student outperforms the teacher and previous state-of-the-art approaches with more complex models and more expensive resources, highlighting the promise of generating weak supervision in the target language. In future work, we plan to extend CLTS for handling cross-domain distribution shift (Ziser and Reichart, 2018) and multiple source languages (Chen et al, 2019). It would also be interesting to combine CLTS with available cross-lingual models, and extend CLTS for more tasks, such as cross-lingual named entity recognition (Xie et al, 2018), by considering teacher architectures beyond bag-of-seed-words.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that even a simple student outperforms the teacher and previous state-of-the-art approaches with more complex models and more expensive resources, highlighting the promise of generating weak supervision in the target language. In future work, we plan to extend CLTS for handling cross-domain distribution shift (Ziser and Reichart, 2018) and multiple source languages (Chen et al, 2019). It would also be interesting to combine CLTS with available cross-lingual models, and extend CLTS for more tasks, such as cross-lingual named entity recognition (Xie et al, 2018), by considering teacher architectures beyond bag-of-seed-words.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, how pre-training can be incorporated into different MNMT architectures is important as well. Recent advances in cross-lingual word [6,17,33,66,75,100] and sentence embeddings 13 [7,20,34,46] could provide directions for this line of investigation. Currently, transfer learning through unsupervised pre-training on extremely large corpora and unsupervised NMT is gaining momentum and we believe that investing in these two topics or a merger between them will yield powerful insights into ways to incorporate large amounts of knowledge into translation systems.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Very recently, unsupervised CLSA methods that do not require either cross-lingual supervision or target language supervision have been proposed (Chen et al, 2018b,a). Chen et al (2018a) transfer sentiment information from multiple source languages by jointly learning language invariant and language specific features. Yet, these unsupervised CLSA methods rely on unsupervised CLWE which builds on the assumption that pretrained monolingual embeddings can be properly aligned.…”
Section: Related Workmentioning
confidence: 99%
“…Recent studies have shown that CLWE can be obtained in an unsupervised way, i.e., without any cross-lingual resources (Zhang et al, 2017;Artetxe et al, 2018). This motivates fully unsupervised CLSA approaches (Chen et al, 2018a) that do not rely on either target language supervision or cross-lingual supervision. These methods generally involve the following steps:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation